2013
DOI: 10.4025/actascianimsci.v35i2.16731
|View full text |Cite
|
Sign up to set email alerts
|

Micromineral nutritional requirements for weight gain in Canindé goats under grazing in the brazilian semiarid

Abstract: ABSTRACT. The purpose was to estimate the liquid requirements of Zn, Fe, Mn and Cu for weight gain in 46 castrated Canindé goats in grazing system in the Caatinga supplemented with 0, 0.5, 1 and 1.5% levels in relation to live weight. The animals had an initial average body weight of 15.76 ± 0.96 kg. Six animals were slaughtered at the onset of the experiment (16.1 ± 1.15 kg BW) and the rest (n = 40) were randomly distributed into one of the four levels of supplementation. The body composition (mg kg Exigência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
4
3
1
Order By: Relevance
“…EBW, ADG, and EBW gain (EBWG) increased as intake level increased, which was according to the report by Zhang et al (2015). Similar results were also reported by Silva et al (2013), who showed that the EBW and EBWG of Canind e goats with BW varying from 15 to 25 kg increased as feed intake level increased. In our study, for Dorper  Hu ewe lambs, Fe, Mn, Cu, and Zn concentrations in the EBW slightly decreased as intake level increased.…”
Section: Discussionsupporting
confidence: 86%
“…EBW, ADG, and EBW gain (EBWG) increased as intake level increased, which was according to the report by Zhang et al (2015). Similar results were also reported by Silva et al (2013), who showed that the EBW and EBWG of Canind e goats with BW varying from 15 to 25 kg increased as feed intake level increased. In our study, for Dorper  Hu ewe lambs, Fe, Mn, Cu, and Zn concentrations in the EBW slightly decreased as intake level increased.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were reported by Silva et al (2013), who showed that the EBW, EBWG, and trace element content of Canindé goats with BW varying from 15 to 25 kg increased as feed intake level increased. In this study, we found that when the Zn, Fe, Cu, and Co contents were expressed based on the metabolic weight (mg/kg 0.75 of EBW) (Table 3), a linear increase was observed in response to the increased level of supplementation.…”
Section: Discussionsupporting
confidence: 77%
“…Net iron requirements in this study (42.45 to 59.03 mg of Fe/BW gain) were similar to those recommended by NRC (2007) for growing sheep (55 mg of Fe/kg of BW gain) and to those found by Zang et al (2015) for males (56.60 to 49.40 mg of Fe/BW gain); however; they were greater than those observed for females (24.70 to 17.60 mg of Fe/BW gain). In our study, all the net requirements for growth were higher than those observed by Silva et al (2013) working with animals in similar conditions to those of this study. According to Zang et al (2015), these differences might be related, in part, to breed, feed, management practices, and physiological and environmental conditions.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations